2014
DOI: 10.1016/j.jss.2014.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Hind limb ischemia–reperfusion injury in diet-induced obese mice

Abstract: Background Obesity is a major risk factor for the development of diabetes. Limb ischemia reperfusion injury (IR) is a common clinical problem in diabetics who have compromised lower extremity perfusion. This study compared the histologic, metabolic and functional outcomes following hindlimb IR in diet-induced obese(DIO) and non-diabetic (ND) mice during the acute and the regenerative phases of IR. Methods DIO and ND mice were subjected to 1.5hrs unilateral hindlimb ischemia followed by 1 or 28 days IR. Muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 44 publications
3
34
0
Order By: Relevance
“…Age-matched male C57BL6 mice were acquired from Jackson Laboratory (Bar Harbor, ME) and were continuously fed with high fat diet consisted of 60% kcal derived from fat for 26 weeks to induce obesity, insulin resistance, and diabetes [21]. Male DIO mice were enrolled in this study since they are more susceptible to developing metabolic syndrome and diabetes compared to females [2224].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Age-matched male C57BL6 mice were acquired from Jackson Laboratory (Bar Harbor, ME) and were continuously fed with high fat diet consisted of 60% kcal derived from fat for 26 weeks to induce obesity, insulin resistance, and diabetes [21]. Male DIO mice were enrolled in this study since they are more susceptible to developing metabolic syndrome and diabetes compared to females [2224].…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis was performed as previously described [21]. Briefly, harvested hind limb muscle tissues were solubilized using lysis buffer containing 50 mM Tris-HCl, pH 7.4, 150 mM NaCl, 1mM EDTA, 1% Nonidet P-40, 5 mM Na 3 VO 4 , 20 mM NaF, 10 mM sodium pyrophosphate and a protease inhibitor cocktail.…”
Section: Methodsmentioning
confidence: 99%
“…Age-matched C57BL6 male mice were acquired from Jackson Laboratory (Bar Harbor, ME) after being fed a diet consisting of 60% kcal from fat for 26 weeks to induce obesity, insulin resistance, and diabetes 16 . To induce hind limb ischemia, all mice were subjected to unilateral femoral artery ligation surgery (FAL) in one hind limb or sham surgery in the contralateral hind limb and then were allowed to recover for two weeks as previously described 17, 18 .…”
Section: Methodsmentioning
confidence: 99%
“…100µg soluble protein aliquots isolated from hind limb tissue using RIPA extraction buffer were subjected to Tris-HCl-SDS electrophoresis and electroblotting transfer followed by chemiluminescence detection as previously described 16 . To detect protein markers of autophagy, the membranes were incubated with an IgG against the microtubule-associated protein light chain-3B (LC3B, Cell Signaling, Danvers, MA), and rabbit monoclonal anti-Beclin-1 (Cell Signaling, Danvers, MA).…”
Section: Methodsmentioning
confidence: 99%
“…Using hind limb ischemia model, Albadawi, et al [58] has shown that diet-induced obesity in mice demonstrated defective functional recovery during the regenerative phase of limb ischemia-reperfusion injury. This finding could be of strong relevance to perfusion of lower extremity in patients with metabolic syndrome and insulin resistance.…”
Section: Experimental Evidence Of CLI In Obesitymentioning
confidence: 99%